Operatory biliary - manometry: instrument and technique - Farcic, Antonio; Delgado, Bolívar; Armand Ugon, César; Belloso, Rogelio (Cirugía del Uruguay, 1977)
In the case of a woman suffering from carcinoma of axilary sweat gland, precisa diagnosis was established; therapy consisted solely of surgery and evolution has been acceptable. A review of this disease is included in the paper.